1999
DOI: 10.1164/ajrccm.159.2.9804051
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Sleepiness to Respiratory Disturbance Index

Abstract: Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
289
13
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(340 citation statements)
references
References 26 publications
24
289
13
14
Order By: Relevance
“…2 It has long been recognized that there is a poor relationship between the AHI-defined severity of OSA and the degree of daytime sleepiness. [24][25][26][27] It remains unclear why one individual with an AHI of 15 may be sleepy whereas another may be asymptomatic. 28 This poor correlation between AHI and ESS is reflected in our WASHS cohort data (r = 0.18).…”
Section: Figure 4-crash Rate and Subjective Sleepiness For Men And Womenmentioning
confidence: 99%
“…2 It has long been recognized that there is a poor relationship between the AHI-defined severity of OSA and the degree of daytime sleepiness. [24][25][26][27] It remains unclear why one individual with an AHI of 15 may be sleepy whereas another may be asymptomatic. 28 This poor correlation between AHI and ESS is reflected in our WASHS cohort data (r = 0.18).…”
Section: Figure 4-crash Rate and Subjective Sleepiness For Men And Womenmentioning
confidence: 99%
“…6 In Japan, the prevalence of BMI X30 in 2004 was much lower at 3% among adults aged 15 years or older. 7 The prevalence of SDB (apnea-hypopnea index (AHI), X15) was 9-14% for western adult men [8][9][10] and 5-10% for their Asian counterparts. 11,12 We previously reported that SDB was positively associated with overweight and excessive daytime sleepiness among Japanese adults.…”
Section: Introductionmentioning
confidence: 99%
“…61,62 All of the studies discussed earlier showed that lower ESS scores and BMI in patients with stroke or HF and OSA cannot be explained by differences in the severity of OSA or other confounding factors and that those are not sensitive independent predictors of the presence of OSA. 63 Therefore, regardless of the underlying mechanisms, lower ESS scores and BMI may make the diagnosis of OSA less likely in the rehabilitation period, and as a result may have a negative impact on clinical course and outcome.…”
Section: Why Obstructive Sleep Apnea Is Under-recognized In Stroke Anmentioning
confidence: 99%